High Risk of Type 2 Diabetes Mellitus among Working Adult - Anindhita Syahbi Syagata (Universitas Islam Negeri Walisongo Semarang, 2019)
This study aims to understand the relation between energy intake and waist circumference with the risk of T2DM. It was an observational study with a cross-sectional design using secondary data (ethical number, 476/KEP-UNISA/V/2018). Sample collected by simple random sampling. The minimum sample size was calculated using the Fisher formula. In this study, obtained 67 sample with inclusion criteria were not taking drugs to lower blood glucose levels. The independent variable in this study was T2DM risk, while the dependent variable was diet and waist circumference. The normality test of data used Kolmogorov-Smirnov. The Spearman correlation analysis used for knowing the relation between energy intake and waist circumference with blood glucose. The result showed that there was no relation between energy intake and blood glucose (r=0.19; p=0.12). There was no relation between waist circumference and blood glucose (r=0,18; p=0,16). There were 91 % of subjects having a high risk of T2DM and 52.2 % of subjects having a high total cholesterol. There is no relation either energy intake or waist circumference and blood glucose. Almost all subjects have high risk in T2DM.